PESTICIDES AND THEIR EFFECTS ON ANIMAL ORGANISMS (LITERATURE REVIEW) - Ismatovna, Xudoyarova Santalat; Tursinbayevich, Isayev Mashrab (Research Focus International Scientific Journal, 2026)
This article, based on literature data, summarizes and examines the types of pesticides, their mechanisms of action, routes of penetration into the body, methods of application, their safe use in agriculture, animal husbandry and veterinary medicine, food safety, as well as problems arising from the improper use of pesticides.